Accuracy of Digital Images in the Detection of Marginal Micro leakage: An In Vitro Study - Alvarenga, Fabio Augusto de Santi [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Pinelli, Camila [UNESP]; Rastelli, Alessandra Nara de Souza [UNESP]; Victorino, Keli Regina [UNESP]; Monteiro Loffredo, Leonor de Castro [UNESP] (Quintessence Publishing Co Inc, 2012)
Purpose: To evaluate the accuracy of Image Tool Software 3.0 (ITS 3.0) to detect marginal microleakage using the stereomicroscope as the validation criterion and ITS 3.0 as the tool under study.Materials and Methods: Class V cavities were prepared at the cementoenamel junction of 61 bovine incisors, and 53 halves of them were used. Using the stereomicroscope, microleakage was classified dichotomously: presence or absence. Next, ITS 3.0 was used to obtain measurements of the microleakage, so that 0.75 was taken as the cut-off point, and values equal to or greater than 0.75 indicated its presence, while values between 0.00 and 0.75 indicated its absence. Sensitivity and specificity were calculated by point and given as 95% confidence interval (95% CI).Results: The accuracy of the ITS 3.0 was verified with a sensitivity of 0.95 (95% CI: 0.89 to 1.00) and a specificity of 0.92 (95% CI: 0.84 to 0.99).Conclusion: Digital diagnosis of marginal microleakage using ITS 3.0 was sensitive and specific.
Keywords: marginal microleakage; diagnosis; validity of tests